Differences in breast cancer outcomes amongst Black US-born and Caribbean-born immigrants - Barreto-Coelho, Priscila (Breast Cancer Res Treat, 2019)
BACKGROUND: There are few studies that directly investigate disparities in outcome within the African diaspora in the US. We investigated the association between nativity of Black women diagnosed with breast cancer (Caribbean or USA place of birth) and ethnicity, age at diagnosis, treatment, tumor characteristics and outcome. METHODS: The data were obtained from the University of Miami Health System, and Jackson Health System. Individual-level data from 1132 cases was used to estimate hazard rations (HRs) of women born in the Caribbean (Caribbean Blacks, CB) or in the USA (US Black, USB) using Cox proportional hazards regression analysis for overall survival. RESULTS: The cohort contains data from 624 (54.9%) USB women and 507 (45%) CB women diagnosed with breast cancer between 2006 and 2017. Compared to CB patients, USB patients had more Estrogen Receptor negative (31.4% vs. 39.1%, P = 0.018) and triple negative breast cancers (19.6% vs. 27.9%, P = 0.003). CB women presented at more advanced stages III/IV (44.2% vs. 35.2%; P = 0.016). CB patients showed a better overall survival (hazard ratio, HR = 0.75; 95% CI 0.59–0.96; P = 0.024). Overall Black Hispanic patients had a better overall survival (HR = 0.51; 95% CI 0.28–0.93; P = 0.028) compared to non-Hispanic Black patients. CONCLUSION: In conclusion the study found that CB immigrants diagnosed with breast cancer have an improved overall survival when compared with USB patients. This finding suggests that within the African diaspora in the USA, additional factors beyond race contribute to worse outcomes in African Americans.